Improving the Innovation of Appropriate Technology in the Home Industry of Pemindangan in Coastal Communities of Tambaksari Village - SUCIPTANINGSIH, Oktaviani Adhi; PRAJANTI, Sucihatiningsih Dian Wisika; SETYOWATI, Dewi Liesnoor; PRIYANTO, Agustinus Sugeng; MARETTA, Yoris Adi (Journal of Environmental Management and Tourism, 2019)
The purpose of this research is to analyze the improvement of appropriate technology innovation in home industry of pemindangan in coastal community of Tambaksari Village. The research method used is qualitative with case study approach. The subjects of the research were the home industry of pemindangan , while the informant was the Tambaksari community and the consumers of pindang fish. The method of data collection used observation, indept interview and documents. Data validity technique used data triangulation and data analysis technique used nvivo data analysis technique. The results showed that there was an increase in production quality in home industry of pemindangan using precise technology pan presto pindang pangkon . The production process becomes time-saving, cost-effective and energy-efficient, in addition to the more hygienic production process and the result of pindang fish is more durable. The benefits are increasing to improve the life quality of pemindangan home industry shoppers. The conclusion is that pindang pangkon is one of the appropriate technological innovations that can be used in home industry of pemindangan.